Link Between the Teeth, Gums and General Health, are we Aware? - Sajjan, Suresh (Biology, Engineering, Medicine and Science Reports)
We all understand that health of the whole body reflects on the face to call face as the mirror of the whole body. To be more specific the oral cavity is the mirror of the health of the individual. Whenever a person falls ill and report to the general physician, after listening to the history the physician will look for some signs in the oral cavity. Thus oral cavity works as gateway for the assessment of general health. Fitting to the saying “we are what we eat”. However the physician would miss out to visualise the teeth while tongue projected out will be covering the teeth.1 The teeth in the oral cavity play a major role in the maintenance of the general health. Researchers have shown there is a greater link between periodontal health and systemic diseases. Recently, evidence has shown that certain common oral infections play a significant role in ATH (Atherosclerosis). The cardiac condition is linked to the periodontal (gums) health of the teeth. The pancreatic disorders are been linked to the health of the periodontium. Further on diabetes, Alzheimer’s, cancer, pancreatic cancer, miscarriages, high blood pressure and obesity are linked with periodontal health. Earlier it was thought as the bacteria are the linkage, however the recent researches have inferred that the inflammation may be the association. Treating this inflammation would help to overcome the periodontal health as well as the chronic inflammatory conditions of the body.2 The maintenance of the periodontal health in the medically compromised patients can prevent some of the complications. However the medical fraternity is ignorant of some of the facts of the oral cavity.